2017
DOI: 10.1088/1361-6668/aa65a2
|View full text |Cite
|
Sign up to set email alerts
|

Feedback solutions for low crosstalk in dense arrays of high-TcSQUIDs for on-scalp MEG

Abstract: Magnetoencephalography (MEG) systems based on a dense array of high critical temperature (high-Tc) superconducting quantum interference devices (SQUIDs) can theoretically outperform a state-of-the-art MEG system. On the way towards building such a multichannel system, we evaluate feedback methods suitable for use in dense high-Tc SQUID arrays where the sensors are in very close proximity to the head (on-scalp MEG). We test on-chip superconducting coils and direct injection of the feedback current into the SQUI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Herein, we demonstrated a number of additional benefits of direct injection of current into the SQUID loop. First, it can be used to couple flux into the SQUID loop, thus eliminating the need for additional coils for SQUID tuning and feedback [49]. Second, the demonstrated temperature independence of the sensor's responsivity (dV /dB) with this approach allows confidence in the calibration even when the temperature of the sensor varies by several kelvin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Herein, we demonstrated a number of additional benefits of direct injection of current into the SQUID loop. First, it can be used to couple flux into the SQUID loop, thus eliminating the need for additional coils for SQUID tuning and feedback [49]. Second, the demonstrated temperature independence of the sensor's responsivity (dV /dB) with this approach allows confidence in the calibration even when the temperature of the sensor varies by several kelvin.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, we found that by using direct injection of current as the feedback method [49], the responsivity dV /dB of a magnetometer operated in a flux-locked loop (FLL) with direct readout can be made temperature independent. The transfer function of a SQUID operated in a FLL with direct readout is V F LL Φ = R f /M f , where R f is the feedback resistance (30 kΩ for our electronics) and M f the mutual inductance between the feedback coil and the SQUID loop [33].…”
Section: Temperature Dependent Magnetometer Calibrationmentioning
confidence: 99%
“…This crosstalk is manifested via mutual inductance between the SQUID feedback signals. However, the crosstalk between high- T c sensors can be reduced to less than 0.5% via direct injection of the feedback current into the SQUID loop, even when the spacing between neighboring sensors is reduced to 1 mm 56 . The helmet design is advantageous with regard to the density of sensor packing as all sensors share the same thermal insulation.…”
Section: Methodsmentioning
confidence: 99%
“…The cryostat houses seven single layer YBa 2 Cu 3 O 7−x (YBCO) SQUID magnetometers, each of which has a directly coupled pickup loop. The current design is similar to the one our group has used for magnetometers in single channel cryostats [10,11], but has been adapted to allow for dense sensor packing with on-chip feedback [15]. Each hairpin SQUID includes a pair of grain boundary Josephson junctions and is made on a 10 mm × 10 mm SrTiO 3 (STO) bicrystal substrate with a misorientation angle of 22.6 • (Shinkosha, Japan).…”
Section: High-t C Squid Magnetometersmentioning
confidence: 99%
“…This approach is favorable for densely-packed SQUIDs in an on-scalp MEG system as it eliminates the need for an additional feedback coil i.e., it is a simple onchip method that compromises neither the standoff distance nor the thermal connection of the sensors to the LN 2 . It furthermore leads to low sensor-tosenor feedback crosstalk (less than 0.5% between adjacent magnetometers) [15].…”
Section: High-t C Squid Magnetometersmentioning
confidence: 99%